(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The laser technology of applying an image to the material has been studied, the most optimal modes of laser engraving have been selected, and products decorated with a laser have been made. It is shown that at present, decorating clothes with a laser is the most economical and unique technology for its decoration.